ANALYZING THE PRACTICE OF MATERIAL ADVERSE CHANGE: A POST PANDEMIC MERGER AND ACQUISITIONS CONTRACT NON-PERFORMANCE CLAUSE FROM THE PERSPECTIVE OF UNIDROIT PRINCIPLES OF INTERNATIONAL COMMERCIAL CONTRACT - Divanadia, Dessandra; Rosadi, Sinta Dewi; Trisnamansyah, Purnama (Transnational Business Law Journal, 2024)
The uncertain conformity between the characteristics of the condition attributable to the inability of mergers and acquisition contract performance due to COVID-19 and the characteristics of force majeure and hardship leads to the use of material adverse change (MAC) as an alternative clause for contract non-performance as a perennial consequence of COVID-19 pandemic in the post pandemic era. This study aims to analyze the implications of COVID-19 pandemic with the use of MAC according to the laws of the nations and the adherence of MAC as a clause with UNIDROIT’s six general principles of international contract during and post pandemic as issued in UNIDROIT Principles of International Commercial Contract. The method of writing used was normative juridical approach with descriptive analytical research specifications. The writing process taken in drafting this study was through a process of literature review from primary, secondary, and tertiary sources. Data analysis method used in this study was through qualitative juridical normative method. The outcome of the analysis shows that the use of MAC as an alternative clause for contract non-performance differs between one national law to another; one of the outstanding characteristics is that the basis of the use of MAC depends on the agreed definition and the burden of proof of MAC set forth in the contract. The use of MAC as an alternative clause for contract non-performance in mergers and acquisitions is compliant with UNIDROIT’s principles of international contract, with considerations of the limitations and exceptions of the international contract principles.